1987
DOI: 10.1128/iai.55.8.1936-1939.1987
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the plasma kallikrein-kinin system by Vibrio vulnificus protease

Abstract: Vibrio vulnificus protease enhanced hypodermic vascular permeability when injected into the dorsal skin of a guinea pig. Enhancement of permeability was observed within 2 min, and the permeability-enhancing reaction terminated at about 10 min postinjection. The permeability-enhancing reaction was greatly augmented by simultaneous injection of a kininase II inhibitor, whereas the reaction was inhibited by soybean trypsin inhibitor, a well-known inhibitor of plasma kallikrein. Furthermore, in vitro activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…These results indicate that V. vulnificus injected into the guinea pig skin enhances vascular permeability by protease action which is an activation of the plasma kallikrein-kinin system. DISCUSSION Previously, we have demonstrated the vascular permeability-enhancing activity of purified preparation of V. vulnificus protease through histamine release and bradykinin generation (10,11,13). Because both histamine and bradykinin are permeability-enhancing and edema-forming factors also in human, the protease can contribute to development of cutaneous lesions characterized by formation of erythema, edema, or ulcer, which are pathognomonic symptoms of human V. vulnificus infection.…”
Section: Vascular Permeability-enhancing Activity Of Protease-deficiementioning
confidence: 86%
See 2 more Smart Citations
“…These results indicate that V. vulnificus injected into the guinea pig skin enhances vascular permeability by protease action which is an activation of the plasma kallikrein-kinin system. DISCUSSION Previously, we have demonstrated the vascular permeability-enhancing activity of purified preparation of V. vulnificus protease through histamine release and bradykinin generation (10,11,13). Because both histamine and bradykinin are permeability-enhancing and edema-forming factors also in human, the protease can contribute to development of cutaneous lesions characterized by formation of erythema, edema, or ulcer, which are pathognomonic symptoms of human V. vulnificus infection.…”
Section: Vascular Permeability-enhancing Activity Of Protease-deficiementioning
confidence: 86%
“…Purified L-180 protease injected into dorsal skin of guinea pig is known to enhance vascular permeability through activation of the plasma kallikrein-kinin system (11). Thus, we next studied effect of SBTI, a specific inhibitor for plasma kallikrein, on the permeability enhancement by living cells.…”
Section: Vascular Permeability-enhancing Activity Of Protease-deficiementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the many endogenous proteases, such as plasmin, Hageman factor and kallikrein, that can initiate the plasma protease cascade system [22], it was found that several microbial proteases (e.g. from Serratia marcescens [5,12], Vibrio uulnificus [14], Candida albicans [6] and many other microorganisms [15]) also do the same. During our 110 study on P. gingivalis, we found that its substrate specificity for synthetic substrate was indeed identical to that of plasma kallikrein and to that of activated Hageman factor.…”
Section: Introductionmentioning
confidence: 99%
“…The permeability-enhancing reaction of VVP was significantly augmented by administration of the kininase inhibitor, while the specific inhibitor for activated factor XII or plasma kallikrein abolished the reaction almost completely. 19,20 Subsequent in vitro studies using human proteins strongly suggested the activation of the human cascade through the limited proteolysis of two zymogens: factor XII and plasma prekallikrein. When the purified VVP was allowed to act on these human zymogens, after a few minutes lag period, both zymogens were directly converted to the active enzymes through digestion of the N-terminal propeptides.…”
Section: Toxic and Pathological Actions Of The Metalloproteasementioning
confidence: 99%